MEDIA AND PENAL POPULISM IN THE EXPANSION OF LIQUID CRIMINAL LAW (Lex localis - Journal of Local Self-Government, 2025)
The article that follows explores the influence of populism in the media and in the criminal sphere on the dissemination of liquid Criminal Law, which is defined as a form of punishment characterized by its adaptability, excess, and an absence of guarantees in today's societies. It investigates how elements such as post-truth, fake news and the strategic use of law, driven by the media, create a perception of social insecurity that supports requests for an increase in punitive intervention. Likewise, penal populism is analyzed as a political-criminal strategy that, using fear, intensifies the figure of the victim and demonizes the offender, which leads to an excessive application of the right to punish, undermining fundamental principles such as legality, proportionality and the presumption of innocence. Through a theoretical analysis and a review of the literature, it is argued that these dynamics promote an expansion of the penal system, modify the interaction between politics, law and society, and strengthen a model of social control that is more symbolic than preventive. Finally, it considers the dangers of this process for the protection of human rights and the challenges faced by the rule of law in an environment characterized by globalization, inequality and the culture of control.